1967
DOI: 10.3758/bf03330765
|View full text |Cite
|
Sign up to set email alerts
|

Similarity and cooperation received as determinants of cooperation rendered

Abstract: Similarity and cooperation received as determinants of cooperation renderedS's perception of high similarity between himself and a fictitious P produced high cooperation and high expectation of cooperation by P. A similar P's ostensible competitive behavior produced retaliation, and a dissimilar or control P's cooperation produced some exploitation. Cooperation by a similar P, and competition by dissimilar or control Ps led to no changes in S's previous strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1968
1968
1982
1982

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 3 publications
1
19
0
Order By: Relevance
“…Initial expectations, formed on the basis of prebargaining information obtained about the opponent, are either confirmed or disconfirmed by the other's behavior. A bargainer expects more conciliatory behavior from a similar than from a dissimilar opponent (Abric & Kahan, 1972;Kaufman, 1967;Krauss, 1966). If he receives the expected cooperative response, he is likely to reciprocate, leading to a quick agreement and a favorable evaluation of that agreement.…”
Section: *1mentioning
confidence: 99%
See 1 more Smart Citation
“…Initial expectations, formed on the basis of prebargaining information obtained about the opponent, are either confirmed or disconfirmed by the other's behavior. A bargainer expects more conciliatory behavior from a similar than from a dissimilar opponent (Abric & Kahan, 1972;Kaufman, 1967;Krauss, 1966). If he receives the expected cooperative response, he is likely to reciprocate, leading to a quick agreement and a favorable evaluation of that agreement.…”
Section: *1mentioning
confidence: 99%
“…If he receives the expected cooperative response, he is likely to reciprocate, leading to a quick agreement and a favorable evaluation of that agreement. If, on the other hand, his expectations are disconfirmed by receiving few concessions, he is likely to retaliate by reducing his own concessions (Kaufman, 1967;Tedeschi, Schlenker, & Bonoma, 19751, leading to deadlock and dissatisfaction. This reasoning suggests that:…”
Section: *1mentioning
confidence: 99%
“…There is evidence that liking for a person arouses the expectancy that the other will provide benefits, while disliking arouses the opposite expectancy (Kaufmann, 1967). It is plausible that under high attraction Ss set higher comparison levels (Le., expected gains from the interaction) than Ss under low attraction.…”
mentioning
confidence: 99%
“…Research by Krauss (1966), Swingle (1966), and Kaufmann (1967) has shown that interpersonal attraction has a beneficial effect on bargaining. But it is by no means an unequivocal prediction to state that attraction will enhance cooperation even more when threats are present.…”
mentioning
confidence: 99%